2005
DOI: 10.1038/sj.leu.2403806
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prognostic significance of karyotype abnormalities in de novo primary myelodysplastic syndromes: a study on 331 patients from a single institution

Abstract: The impact of clinical parameters, International Prognostic Scoring System (IPSS) scores/cytogenetic categories, and some single cytogenetic defects on overall survival (OS) and time to myelodysplastic syndromes (MDS)/AML progression (progression-free interval (PFI)) was evaluated in 331 MDS patients. Statistical analysis demonstrated that OS and PFI were significantly affected by all these parameters. Since single 7q-showed a better survival than the poor IPSS cytogenetic category (P ¼ 0.009), it was consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
66
1
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 35 publications
(56 reference statements)
9
66
1
4
Order By: Relevance
“…In our series, clonal chromosomal abnormalities were revealed in 53.8% of the 630 de novo consecutive MDS patients. This frequency is similar to that reported by other studies [3][4][5][6][7][8][9][10][11][12][13]16,17], even if it should be underlined that our study did not include patients diagnosed as RAEB in transformation (RAEB-t), now considered AML by the WHO classification. Instead, the NCCSS study [17] also analyzed RAEB-t patients, as the exclusion of this MDS FAB subtype led to a statistically lower risk in the entire sample without affecting the relative position of the five prognostic subgroups.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In our series, clonal chromosomal abnormalities were revealed in 53.8% of the 630 de novo consecutive MDS patients. This frequency is similar to that reported by other studies [3][4][5][6][7][8][9][10][11][12][13]16,17], even if it should be underlined that our study did not include patients diagnosed as RAEB in transformation (RAEB-t), now considered AML by the WHO classification. Instead, the NCCSS study [17] also analyzed RAEB-t patients, as the exclusion of this MDS FAB subtype led to a statistically lower risk in the entire sample without affecting the relative position of the five prognostic subgroups.…”
Section: Discussionsupporting
confidence: 91%
“…The IPSS [8], the Spanish MDS Cytogenetic Working Group [10] and another study [16] have reported that del(7q) and 27 present a similar poor OS and a similar high risk of MDS/AML evolution. In contrast, the GA data set [13] and other reports [11,12,37] have revealed that isolated del(7q) and 27 were associated with an intermediate and a poor clinical outcome respectively. In particular, two previous studies by our own group [11,12] revealed that in univariate and multivariate analyzes del(7q) was associated with a survival probability better than that of the poor IPSS cytogenetic category and similar to that of the intermediate category, whereas the risk of MDS/AML evolution was similar to those of both IPSS cytogenetic categories.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations